Trafficking and the conscience of humanity: a social and legal examination of child trafficking - May, Larry (Routledge, 2024)
"Human trafficking has become the scourge of the 21st century, with child trafficking arguably its worst form. Yet there is only a patchwork legal regime trying to deal with child trafficking. Trafficking and the Conscience of Humanity assesses this legal regime, arguing that a more coordinated and international response is needed"--